Hydrogen desorption behaviour and microstructure evolution of a γ-AlH3/MgCl2 nano-composite during dehydriding. Issue 78 (4th August 2016) - Duan, Congwen; Hu, Lianxi; Sun, Yu; Wan, Zhipeng
Abstract : A deep insight into the mechanism of the dehydriding reaction of γ-AlH3 nano-composite. Abstract : A γ-AlH3 /MgCl2 nano-composite, without or with Zn and Zr doping, was synthesized by solid state reaction milling using MgH2 and AlCl3 as reagents. The hydrogen desorption behaviour of the nano-composite was investigated by temperature programmed de-hydriding (TPD) and differential scanning calorimetry (DSC) tests, and the microstructure evolution due to de-hydriding was characterized by XRD, SEM, and TEM respectively. For de-hydriding by heating from 40 to 320 °C, a three-stage featured TPD curve was observed, with the maximum hydrogen desorption capacity excluding the MgCl2 in the composite achieving about 9.71 wt% when the temperature was raised to 240 °C and then remaining unchanged for the subsequent heating process to 320 °C. DSC and XRD tests revealed that three individual events, i.e., the transformation of γ-AlH3 to α-AlH3 phase, the direct decomposition of γ-AlH3 phase, and the subsequent decomposition of the α-AlH3 phase, take place during the de-hydriding process of the γ-AlH3 /MgCl2 nano-composite. By doping the nano-composite with elements Zn and Zr, an improvement in the de-hydriding kinetics was observed. According to the calculation based on the fitting of de-hydriding kinetics data, it was found that the addition of Zn and Zr can reduce the activation energy for the de-hydriding reaction. Also, both the de-hydriding mechanism and the role that Zn and Zr play in the de-hydriding process were interpreted based on TEM observations.